2006
DOI: 10.1016/j.vibspec.2006.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the VROA signals of helical heptasilanes using an atomistic approach

Abstract: The VROA signatures of different helical conformers of heptasilane have been analyzed using an atomistic approach. Based on ab initio VROA quantities, the decomposition scheme and its representation under the form of group coupling matrices enable us to highlight the dominant role of the Si atoms for the modes studied. The sum of the contributions from H atoms, on the other hand, is generally negligible, often due to compensations, whereas the heteronuclear Si-H contributions can be important. The dominating V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…This analysis highlighted the dominant role of the Si atoms in the VROA intensities of the key vibrations as well as the collective character of these vibrations. [20] Another investigation of oligomeric systems, carried out on polyethylene chains, confirmed the higher sensitivity of VROA to helicity with respect to the conventional Raman technique. [21] This study further demonstrated the relevance of using the rDPS:3-21G basis set introduced by Zuber and Hug [22] to evaluate the three optical polarizability tensors, or more precisely their variations upon geometry distortions.…”
mentioning
confidence: 77%
“…This analysis highlighted the dominant role of the Si atoms in the VROA intensities of the key vibrations as well as the collective character of these vibrations. [20] Another investigation of oligomeric systems, carried out on polyethylene chains, confirmed the higher sensitivity of VROA to helicity with respect to the conventional Raman technique. [21] This study further demonstrated the relevance of using the rDPS:3-21G basis set introduced by Zuber and Hug [22] to evaluate the three optical polarizability tensors, or more precisely their variations upon geometry distortions.…”
mentioning
confidence: 77%
“…[65][66][67][68][69] In particular, specific signatures of characteristic conformations, such as a helices and b sheets [36,37,48,49] and helical pitch, [65,[67][68][69] have been highlighted throughout all these studies. Therefore, the aim of this article is to search for VROA patterns associated with the angle between the two naphthalene rings and to see whether bands change sign on going from the cisoid to the transoid form, as observed for electronic CD and VCD spectroscopies.…”
mentioning
confidence: 99%
“…Indeed, although the description of the normal modes of vibration is similar for both compounds, their relative intensities are different. In this respect, we are undergoing a study on the decomposition of the VROA signals in terms of atomic contributions for polysilane 49 and polyethylene. Nevertheless, although such conformational signatures have been employed to study protein dynamics 12–14, VROA signatures of helical polymers have not yet been demonstrated experimentally.…”
Section: Discussionmentioning
confidence: 99%